Parametric study of coupled vane compressor - Ong, Jia Jie (Nanyang Technological University, 2023)
Positive displacement rotary compressors have been widely used in household and industry applications. Due to high demand for higher efficiency, more sustainable and higher energy efficient compressors are research into and developed. Thus, a new rotary compressor known as Coupled Vane Compressor (CVC) was invented in 2019 intended to meet this demand. The new design introduces use of two coupled vanes which slide diametrically through the rotor. The design of the CVC reduces materials required during manufacturing without compromising its energy efficiency. Mathemathical and computer models have been formulated in ForTran programming language to simulate the performance of the compressor numerically. In this project, the model has been used to determine and understand the operational characteristics of CVC. It is with intention that through these studies, especially the effects of design parameters on the performance of the compressor, design improvements can be proposed to further improve operational characteristics of the CVC.